Comparison of Legal Maxims in Common Law and Islamic Law: Similarities and Differences in Dispute Resolution - Wahyudi; Suntana, Ija (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
This study compares legal maxims or legal principles in common law and Islamic law, focusing on the similarities and differences in applying these rules in dispute resolution. The legal maxim in these two legal systems is a fundamental principle that guides judges and legal practitioners in interpreting legal rules and deciding cases. In common law, legal maxims develop through precedent and jurisprudence. In contrast, in Islamic law, this rule comes from religious texts such as the Qur'an and Hadith, as well as the development of law by scholars. The normative-comparative approach method is used to analyze the similarities and differences of the maxim legal in both legal systems. This method helps identify important points of similarity and differences and reveals ways in which the two legal systems can complement each other. This comparative study concludes that Common Law and Islamic Law originate from different foundations, secular precedent versus divine revelation; they share a fundamental commitment to justice, embodied in maxims like